trans-Dibromidobis(triphenylphosphine-κP)palladium(II) chloroform monosolvate - Lo, Kong Mun (International Union of Crystallography, 2009)
The Pd(II) atom in the title compound, [PdBr(2){P(C(6)H(5))(3)}(2)]·CHCl(3), lies on a twofold rotation axis and is coordinated in a distorted square-planar geometry by two P atoms from two triphenylphosphine ligands and by two Br atoms in a trans arrangement. The chloroform solvent molecule is equally disordered about another twofold rotation axis.